2005
DOI: 10.1159/000083870
|View full text |Cite
|
Sign up to set email alerts
|

Extraintestinal Manifestations of Crohn’s Disease

Abstract: In each case of extraintestinal manifestations of Crohn’s disease, active disease, if present, should be treated to induce remission, which may positively influence the course of most concomitant extraintestinal manifestations. For some extraintestinal manifestations, however, a specific treatment should be introduced. This latter part of disease management will be discussed in this chapter, in particular for pyoderma gangrenosum, uveitis, spondylarthropathy – axial arthropathy – and primarysclerosing cholangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 129 publications
1
23
0
3
Order By: Relevance
“…The precision of each CD category was therefore evaluated by documenting criteria included in the definitions proposed for broad clinical categories of CD [6,7,8,9,10,11,12]. If the medical record reported at least one of the criteria from the definitions and included supporting documentation, this element was considered as ‘present and precise’.…”
Section: Methodsmentioning
confidence: 99%
“…The precision of each CD category was therefore evaluated by documenting criteria included in the definitions proposed for broad clinical categories of CD [6,7,8,9,10,11,12]. If the medical record reported at least one of the criteria from the definitions and included supporting documentation, this element was considered as ‘present and precise’.…”
Section: Methodsmentioning
confidence: 99%
“…This review is an updated version of a prior publication published as a preparatory work for the European Panel on the Appropriateness of Crohn ’ s Disease Therapy (EPACT) held in 2004 [3] and entirely replaces the earlier publication.…”
Section: Introductionmentioning
confidence: 99%
“…This was subsequently expanded manually to include references contained in review articles and references suggested by the panelists. The selected studies were arranged hierarchically according to evidence-based medicine criteria and commented on in a series of review articles [2,3,4,5,6,7,8,9,10,11]. References to the primary studies are to be found in those articles.…”
Section: Methodsmentioning
confidence: 99%